Even Secure Children's Homes Won't Take Me. Children Placed in Alternative Accommodation. Issue 4 (2nd October 2022) - Williams, A.; Cummings, A.; Forrester, D.; Hodges, H.; Warner, N.; Wood, S.
ABSTRACT: Secure Children's Homes (SCH) in the UK are locked establishments for children perceived to be at serious risk and referred through welfare or youth justice systems. The UK SCH population has recently decreased, but the percentage accommodated for welfare concerns has not. It is of concern that some of the children referred to SCHs through the welfare system cannot be placed and are therefore found an alternative accommodation. This article is concerned with children from England referred to SCHs for welfare reasons particularly the process of trying to find a SCH place, the characteristics of children placed in alternative accommodations and the residences used for alternative accommodation. Findings show that two-fifths of the children, typically older males with challenging, offending, or sexually harmful behaviors were not placed in a SCH. While the children's behaviors contributed to SCH refusals, the situations were more nuanced with other contributory factors including children not meeting secure accommodation criteria, non-implementation of secure orders and children entering different secure settings. The study returns attention to the difficulty of finding an SCH place for extremely vulnerable children and raises concerns about current SCH service capacity and the unknown nature of alternative accommodations.